PEMANFAATAN SISA PANEN DALAM BENTUK BOKASHI SEKAM TERHADAP PENINGKATAN BEBERAPA SIFAT KIMIA (pH, C ORGANIK, N, P, DAN K) TANAH SAWAH - Roro Kesumaningwati (PROSIDING SEMINAR KIMIA, 2014)
The purpose of the research was to find out the influence of applicat ion bokashi husk toward availab ility of some characteristic of soil chemistry (pH, C-Organic, N, P, and K). The research was held from September to December 2013 on Jl. Pasir Balengkong, at paranet in front of Agroecotecnology Depart, Faculty of Agriculture Mulawarman University, Samarinda.The analysis result indicated the increase of soil characteristic such as pH with 4,89, C-organik with 2,51 %, Nitrogen with 0,23 %, Phosfor with 1,88 pp m, and 83,44 %.